2022
DOI: 10.1177/03091333221088018
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of winter wheat yield at county level in China using ensemble learning

Abstract: Since increasing food demand and continuous reduction of available farmland, reliable and near-real-time wheat yield forecasts are essential to ensure regional and global food supplies. Although the crop model has been widely used in yield estimation, its applicability in large-scale yield prediction is limited due to the large amount of data required for parameterization. We took the main winter wheat growing areas in China and developed an ensemble learning framework based on seven machine learning algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The ET model can determine the importance of variables based on the contribution of each variable to the model’s prediction (Zhang et al, 2022b). We estimated remotely-sensed drought factors’ importance for predicting 1-, 3-, and 6-month SPEIs by the ET model based on the datasets of all stations and the corresponding stations of each cluster, respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ET model can determine the importance of variables based on the contribution of each variable to the model’s prediction (Zhang et al, 2022b). We estimated remotely-sensed drought factors’ importance for predicting 1-, 3-, and 6-month SPEIs by the ET model based on the datasets of all stations and the corresponding stations of each cluster, respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is crucial to increase the model's robustness to make it suitable for drought prediction in different regions. Stacking is an ensemble approach that combines the strengths of various models and compensates for the shortcomings of just one model (Zhang et al, 2022b). In this study, selected heterogeneous models were integrated as base learners for the Stacking model to learn the advantages of each base learner for better results.…”
Section: Discussionmentioning
confidence: 99%
“…Forecasting the demand for any commodity is one of the most important aspects of preventing wastage in any form. Zhang et al [7] predicted wheat production forecast on a country level using ensemble learning. I. Shah et al [8,9,10,11,12] and N.Bibi et al [13] have suggested many methods to predict the electricity demands and prices for various times, i.e., short term, medium-term, and long-term as well.…”
Section: Literature Surveymentioning
confidence: 99%
“…In recent years, machine learning algorithms have become more popular, particularly deep neural networks, to forecast crop yields. Studies have shown that these algorithms can predict county-level yields up to four months in advance of harvest [18][19][20]. However, it needs a lot of historical data to be trained, and the outcomes of the training on a particular period and region cannot be extended to other times and regions [21,22].…”
Section: Introductionmentioning
confidence: 99%